E-Learning for Transplant Coordinators – Structuring a Unique 'Blended' Initiative for Capacity Building to Promote Organ Transplantation in India. (July 2018) - Navin, Sumana; Suriyamoorthi, Sujatha; Alex, Ann; Shroff, Sunil
Abstract : Introduction: Transplant coordinators are mandated by law in India to be appointed in all hospitals performing transplants. Structured training programs impart transplant coordinators with the necessary skills and capabilities for the job. Currently, programs are conducted face-to-face only and are of one week and one month duration. Many participants are unable to attend because of time constraints. In addition, participants are from different educational backgrounds and have varied skill sets and learning requirements. To meet this challenge, MOHAN Foundation has worked on a structured one year E-Learning programme for working healthcare professionals. It is cost effective, ensures a wider reach of the training, and participants can learn at their own pace. Methods: The course structure comprises E-learning along with face-to-face contact sessions for soft skills, simulations, activities and role play (blended learning). E-learning online modules: 60 modules cover medical, legal, ethical and religious aspects of organ donation and transplantation as well as counseling, grief counseling and transplant coordination. The modules include theory, PowerPoint presentations, video lectures and films, and assignments. Blended learning: One week contact learning, Application oriented field visits, Project. High quality video lectures give the learning a 'live' feel. These feature faculty from both India and abroad and give the participants an international learning experience. The films include key demonstrations on testing for brain stem reflexes, apnea test and Arterial Blood Gas analysis. Self-assessments are included at the end of each module. At the end of the course, the participant takes a final examination and viva voce. The blended component includes face-to-face sessions on soft skills, conflict management, healthcare management, team building, stress management, basics of counseling, and grief counseling. There are also a number of activities, case study discussions, and role plays. Application oriented field visits include visits to a dialysis unit, blood bank, skin bank, and eye bank. Each participant is assigned a 120 hour project to be completed over three months. Results: The E-learning program was launched in September 2017 and seven participants from five states in India, and Bangladesh have enrolled so far. Participants from states such as Jammu & Kashmir, Mizoram, Bihar, Karnataka, and Kerala represent how E-learning can be an important tool to impart education to different geographic areas of India and South Asia. Conclusion: E-learning has the potential to increase the cadre of healthcare professionals dedicated to transplant coordination and grief counseling not only in India, but also South Asia to improve the organ donation rate in this region.